Electron Transporting Bilayer of SnO2 and TiO2 Nanocolloid Enables Highly Efficient Planar Perovskite Solar Cells. Issue 1 (7th January 2020) - Hu, Manman; Zhang, Luozheng; She, Suyang; Wu, Jianchang; Zhou, Xianyong; Li, Xiangnan; Wang, Deng; Miao, Jun; Mi, Guojun; Chen, Hong; Tian, Yanqing; Xu, Baomin; et al.
Abstract : Moisture Stability In article number 1900331, Baomin Xu, Chun Cheng, and co‐workers show that the cascade‐aligned energy levels and the defect‐passivation achieved by combining commercially accessible SnO2 and home‐made TiO2 nanoparticles effectively reduce energy loss and inhibit defects in the device. Consequently, the perovskite solar cell delivers a high power conversion efficiency (PCE) of 20.50%, which is superior to that of control devices based on SnO2 with a PCE of 18.09%.